Ceramic-Supported Alginate Adsorbent for the Removal of Heavy Metal Ions - Chrysoula P. Athanasekou; George E. Romanos; Andreas A. Sapalidis; Nick K. Kanellopoulos (Adsorption Science & Technology)
Hybrid alginate/ceramic support sorbents have been developed by the physical imbibing of an alginic acid solution into silica pores and γ-alumina microspheres. The metal ion-binding capacity of the prepared hybrids was examined by means of batch Cd 2+ ion adsorption experiments. In addition, since the porous γ-alumina microspheres proved capable of retaining higher quantities of alginic acid than silica, they were chosen as a more appropriate substrate for the application of a chemical modification procedure. In this context, the aim was to develop hybrid sorbents with an enhanced stability and adsorption capacity obtained by grafting the bio-molecule onto the substrate. Such chemical modification included grafting two different types of silanes onto the external surface and pores of γ-alumina, followed by chemical bonding of the alginate with the characteristic groups of the silane molecules involved. Such chemically-prepared sorbents exhibited almost twice the Cd 2+ ion adsorption capacity of sorbents prepared by physical imbibing methods. The best uptake achieved in the present work was 1.44 mg Cd 2+ ion/g substrate. Moreover, the adsorption capacity per bonded alginate mass exceeded the capacity often reported in the literature for alginate beads.